ANALISIS KELAYAKAN USAHA PENGGILINGAN PADI DI DISTRIK TANAH MIRING KABUPATEN MERAUKE - Linus Yokta Jehabun; Ineke Nursih Widyantari; Nurliah Nurliah (Agriculture Faculty of Flores University, 2026)
This research aims to find out revenue, income, and feasibility in the Tanah Miring District, Merauke Regency. The research location was purposively selected because the area is one of the rice-producing regions in Merauke Regency. The study used saturated sampling because the population comprised 30 rice mills, which were the research sample. Data were collected through observation, interviews, and questionnaires. The research results show that the revenue of the rice milling business in Tanah Miring District, Merauke Regency, is Rp 3,479,878,333/year. The average income obtained is Rp 322,774,044/year, and the R/C Ratio analysis results show that the R/C Ratio value is 1.10. This result means that the R/C ratio is greater than one, and therefore, the rice milling business in Tanah Miring District, Merauke Regency, is feasible to operate.